Piperonyl butoxide elicits a robust transcriptional response in adult Drosophila melanogaster. - Pfannenstiel, L.J.; Scott, J.G.; Buchon, N. (Pesticide Biochemistry and Physiology, 2024)
While much attention has been devoted to understanding the transcriptional changes underlying resistance to insecticides, comparatively little is known about the transcriptional response of naive insects to agrochemicals. In this study, we analyze the transcriptomic response of an insecticide susceptible strain of Drosophila melanogaster to nine agrochemicals using a robust method that goes beyond classical replication standards. Our findings demonstrate that exposure to piperonyl butoxide (PBO), but not to eight other compounds, elicits a robust transcriptional response in a wild-type strain of Drosophila melanogaster. PBO exposure leads to the upregulation of a subset of Cyps, GSTs, UGTs and EcKls. This response is both time and concentration-dependent, suggesting that the degree of inhibition of P450 activity correlates with the magnitude of the transcriptional response. Furthermore, the upregulation of these enzymes is excluded from reproductive organs. Additionally, different sets of genes are regulated in the digestive/secretory tract and the carcass. Our results suggest that P450s play a role in metabolizing yet unidentified endogenous compounds and are involved in an as-yet-unknown physiological regulatory feedback loop.